2011
DOI: 10.1103/physreva.83.023614
|View full text |Cite
|
Sign up to set email alerts
|

Interspecies singlet pairing in a mixture of two spin-1 Bose condensates

Abstract: We study the ground state properties of a mixture formed by two spin-1 condensates in the absence of an external magnetic field. As the collisional symmetry between interspecies bosonic atoms is broken, the interspecies coupling interaction ($\beta $) and interspecies singlet pairing interaction ($\gamma $) arise. The ground state can be calculated using the angular momentum theory analytically for $\gamma =0$. The full quantum approach of exact diagonalization is adopted numerically to consider the more gener… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 39 publications
(89 reference statements)
1
3
0
Order By: Relevance
“…We have solved the CGP numerically to obtain the solutions for 2-species spin-1 BEC, and we have derived and calculated the probabilities m P X and mn P AB extracted from the solutions. We have confirmed that the previous results under the SMA are qualitatively correct [8,14], and we have demonstrated that the spin-textures and the spin-transition can be identified via the observation of the probabilities. The following points are reminded.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…We have solved the CGP numerically to obtain the solutions for 2-species spin-1 BEC, and we have derived and calculated the probabilities m P X and mn P AB extracted from the solutions. We have confirmed that the previous results under the SMA are qualitatively correct [8,14], and we have demonstrated that the spin-textures and the spin-transition can be identified via the observation of the probabilities. The following points are reminded.…”
Section: Discussionsupporting
confidence: 88%
“…Due to the influence of the spin-dependent interspecies interactions, the spin-textures of 2-species S-BEC become more complicated. These textures have been studied by a number of authors [7][8][9][10][11][12][13][14][15] . In the previous study the single spatial mode approximation has been adopted.…”
Section: Introductionmentioning
confidence: 99%
“…In the p-phase the spins of atom are two-by-two coupled to zero to form the singlet pairs (s-pair), and the total spin of the condensate S = 0. In the f -phase all the spins are fully polarized, i.e., lying along a common direction, and S = N. For 2-species BEC it was found in [7][8][9][10][11][12][13][14][15][16][17] that there are three types of spin-textures, namely, (i) the p+p texture where both species are in p-phase; (ii) the f // f texture where both species are in f -phase, and the two total spins (each for a species) are lying either parallel or antiparallel to each other; and (iii) the f //q texture where one in f -phase and one in quasi-ferromagnetic phase (q-phase, a mixture of aligned spins and s-pairs).…”
Section: Introductionmentioning
confidence: 99%
“…In such two-species system the spin-dependent inter-species interaction can induce various types of spin-changing processes for two different atoms, i.e., the spin-mixing processes A 0 + B 0 A ±1 + B ∓1 as well as the spin-exchanging processes A 0 + B ±1 A ±1 + B 0 and A +1 + B −1 A −1 + B +1 , where A and B denote the atomic species and the subscript 0, ±1 denotes the atomic magnetic quantum number, as above. These processes can induce coherent het- * pengzhang@ruc.edu.cn eronuclear spin dynamics [27,28] and significantly influence the quantum phases of the two-species spin-1 BEC [29][30][31][32][33][34]. In the experiments one can control most of the above spin-changing processes via the bias magnetic field.…”
Section: Introductionmentioning
confidence: 99%